Anticholinesterase Toxicity and Oxidative Stress - Dejan Milatovic; Ramesh C. Gupta; Michael Aschner (The Scientific World Journal)
Anticholinesterase compounds, organophosphates (OPs) and carbamates (CMs) are commonly used for a variety of purposes in agriculture and in human and veterinary medicine. They exert their toxicity in mammalian system primarily by virtue of acetylcholinesterase (AChE) inhibition at the synapses and neuromuscular junctions, leading into the signs of hypercholinergic preponderance. However, the mechanism(s) involved in brain/muscle damage appear to be linked with alteration in antioxidant and the scavenging system leading to free radical-mediated injury. OPs and CMs cause excessive formation of F2-isoprostanes and F4-neuroprostanes, in vivo biomarkers of lipid peroxidation and generation of reactive oxygen species (ROS), and of citrulline, a marker of NO/NOS and reactive nitrogen species (RNS) generation. In addition, during the course of these excitatory processes and inhibition of AChE, a high rate of ATP consumption, coupled with the inhibition of oxidative phosphorylation, compromise the cell's ability to maintain its energy levels and excessive amounts of ROS and RNS may be generated. Pretreatment with N-methyl D-aspartate (NMDA) receptor antagonist memantine, in combination with atropine sulfate, provides significant protection against inhibition of AChE, increases of ROS/RNS, and depletion of high-energy phosphates induced by DFP/carbofuran. Similar antioxidative effects are observed with a spin trapping agent, phenyl-N-tert-butylnitrone (PBN) or chain breaking antioxidant vitamin E. This review describes the mechanisms involved in anticholinesterase-induced oxidative/nitrosative injury in target organs of OPs/CMs, and protection by various agents.